Organotin compounds: effects on the marine fauna – a review - de Castro, Ítalo Braga; Queiroz, Liana Rodrigues; Barreira, Cristina de Almeida Rocha (Arquivos de Ciências do Mar, 2007)
The organotin compounds are used since the1970’s in antifouling paints applied in ships. In the 1980’s the toxic effects of these compounds were detected in oyster Crassostrea gigas cultivated at Arcachon Bay, France. Since then, many organisms around the world have shown the symptoms of this kind of contamination. The present study tried to catalogue most of the marine organisms identi fi ed down to genus or species levels species that, in some way, are affected by organotin compounds and ascertain their occurrence in Brazil. A total of 254 species were identi fi ed among various taxa which undergo changes when exposed to this kind of contamination. Out of those species, 55 belong to genera that are classi fi ed into the Brazilian fauna. It is expected, with this review, that the national scientific community becomes aware of the issues inherent in the contamination by organotin compounds.